Impact of age and sex on survival outcomes in patients aged 1-45 years with acute lymphoblastic leukemia treated according to the stratification used in the NOPHO ALL2008 trial - Lähteenmäki Taalas, Tuomas; Oskarsson, Trausti; Heyman, Mats; Lund, Bendik; Lepik, Kristi; Vaitkevičiene, Goda; Jonsson, Olafur Gisli; Eriksson, Julia; Toft, Nina; Griškevičius, Laimonas; Hallbook, Helene; Palk, Katrin; et al. (Ferrata Storti Foundation (Haematologica), 2025)
Age and sex have historically been associated with differences in acute lymphoblastic leukemia (ALL) survival. In the NOPHO ALL2008 trial, patients aged 1-45 years with BCR::ABL1-negative B-precursor and Tcell ALL were included, but neither sex nor age was integrated into risk group allocation. Among 1,771 trial patients stratified into protocol-appropriate risk groups, we estimated the impact of age and sex on survival (even after relapse) and toxicities prospectively registered at three-month intervals.
In multivariate Cox regression analysis adjusted by sex, age group, and risk group, age but not sex was an independent risk factor for reduced 5-year event-free survival (EFS), hazard ratio 1.57 (95%CI 1.15-2.14) for patients 10-17.9 years, and 2.70 (2.03-3.58) for patients 18-45 years, compared to patients <10 years at diagnosis.
The overall 5-year pEFS was 0.83. For standard-risk patients (B-lineage, white cell count <100x109/l, no risk genetics, minimal residual disease day 29 <0.1%), an inferior 5-year EFS was observed among patients 18-45 years (pEFS 0.78, p=<0.001) and 10-17.9 years (pEFS 0.86, p=0.002) compared to patients <10 years (pEFS 0.93). For the intermediate-risk and high-risk groups, EFS was worse for patients 18-45 years compared to patients <10 years, pEFS 0.69 vs 0.89 (p=<0.001) and pEFS 0.55 vs 0.71 (p=0.005), respectively. Osteonecrosis and veno-occlusive disease were associated with the female sex in standard-risk group, and age ≥10 years was associated with osteonecrosis, thrombosis, and pancreatitis in sex- and treatmentgroup- adjusted analyzes.
In conclusion, this study indicates that risk-grouping and/or treatment-intensity criteria should differ across age groups, and age-adapted strategies to mitigate toxicities are needed.